An interview with Alan Grant. Issue 1 (1st July 2020) - Klaehn, Jeffery
Alan Grant (b. 1949) is a Scottish writer widely known for his work on 2000AD (Anderson: Psi-Division, Judge Dredd, Shamballa, Mazeworld) and for his famous tenures on various titles featuring characters such as Batman and Lobo. He is the co-creator of Anarky, the Ventriloquist, Jeremiah Arkham and Mr Zsasz. This interview, undertaken throughout July and August of 2018, explores a range of topics and issues, including (but not limited to) his thoughts comics as a subversive medium; his collaborations with artists Arthur Ranson and Norm Breyfogle; his Anarky character; comics and politics; Cassandra Anderson as well as the Judge Dredd comics and film adaptations; his 'Greeting from Scotland' story for Nick Fury, Agent of SHIELD; his award-winning graphic novel, The Loxleys and the War of 1812; as well as his current writing projects.